2a=3b=4c then find (a+b+c)/(3a+3b-6c)
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Write a and c in term of b : a = 2 3 b and c = 4 3 b . Now bashing, a + b + c = 2 3 b + b + 4 3 b = 4 1 3 b and 3 a + 3 b − 6 c = 2 9 b + 3 b − 2 9 b = 3 b .
Hence , dividing we get 4 1 3 b × 3 b 1 = 1 2 1 3 ≈ 1 , 0 8 3 3 3
Problem Loading...
Note Loading...
Set Loading...
Substitute a=6, b=4 and c=3. Then given expression becomes 13/12, i.e. 1.083